Determination of the Mechanical Properties of Friction Welded Tube Yoke and Tube Joint - Efe Işık; Çiçek Özes (Advances in Materials Science and Engineering)
This paper deals with the friction welding of the tube yoke and the tube of the drive shaft used in light commercial vehicles. Tube yoke made from hot forged microalloyed steel and the tube made from cold drawn steel, with a ratio (thickness/outside diameter ratio) of less than 0.1, were successfully welded by friction welding method. Hardness distributions on both sides of the welded joint across the welding interface were determined and the microstructure of the joint was investigated. Furthermore, joint strength was tested under tensile, static torsional, and torsional fatigue loadings. The tested data were analyzed by Weibull distribution. The maximum hardness value along the welded joint was detected as 553 Hv1. The lowest detected tensile strength of the joint was 13% less than the base materials’ tensile strength. The torsional load carrying capacity of the friction welded thin walled tubular joint without any damage was obtained as 4.252,5 Nm in 95% confidence interval. After conducting fully reversed torsional fatigue tests, the fatigue life of friction welded tubular joints was detected as 220.066,3 cycles.